Increasing The Effectiveness And Efficiency Of Supply Chain Management In Increasing Customer Loyalty B21 Digital Printing - Annan Putri, Perdana Argi; Raden Johny Hadi Raharjo; Nurul Hasanah (Fakultas Ekonomi Universitas Kadiri, 2023)
Supply Chain Management (SCM) has been implemented in various industries, one of which is B21 Digital Printing, a digital and textile printing facility in Gresik Regency. Supply Chain Management (SCM) is a process and production activity starting from obtaining raw materials and the production process to distributing goods to customers. The obstacle here is the lack of adequate suppliers in accepting requests for raw materials, and this is the primary goal of the research, namely how to increase the effectiveness and efficiency of supply chain management in achieving customer loyalty. The method used in this research is descriptive qualitative research. Research subjects are informants who provide research data through interview sessions. Based on the results of qualitative research using interview and observation techniques as well as data collected by the authors, it can be concluded that developing a structured supply chain management model can maintain and increase customer loyalty.